Increasing scale and effectiveness of private land conservation - Pague, Chris, speaker; Sanderson, John, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The importance of private lands for conservation is increasingly apparent. Private landowners and wildlife managers face many challenges as they work to maintain the ecological, economic and social integrity of these lands. For many years The Nature Conservancy conserved private lands by purchasing them and then establishing nature preserves or transferring lands to public agencies. During the past two decades, conservation easements have become firmly established as the transactional tool of choice for conserving private lands. These tools for land protection remain valuable, yet they are insufficient, in part because the cost of buying land or easements far outstrips the availability of funding sources. There is substantial need and opportunity to develop financial and management tools and techniques that advance agricultural, economic, and conservation outcomes on private lands at a scale that effectively conserves whole landscapes and the species they contain. The Nature Conservancy is investing in several novel approaches, including multi-part transactions that incorporate much greater acreages than traditional transactions, enhancing both economic opportunity and conservation outcomes; increasingly sophisticated conservation easements that foster negotiations with energy developers; market-based sustainable grazing agreements between agricultural producers and buyers; and community-based land management programs that enhance both conservation and economic returns. Working in collaboration with private landowners, state and federal agencies, and academic researchers, we are analyzing vulnerabilities of private lands and demonstrating adaptation strategies that may increase resilience of socio-ecological systems including private lands.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Chris Pague.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses